1977
DOI: 10.1172/jci108733
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of sodium transport by prostaglandin E2 across the isolated, perfused rabbit collecting tubule.

Abstract: A B S T RAC T This study was designed to examine whether prostaglandin E2 can directly affect sodium transport across isolated perfused rabbit renal collecting tubules. Changes in transepithelial potential and isotopic sodium fluxes in response to peritubular prostaglandin E2 were measured. In addition, changes in transepithelial potential of the outer medullary collecting tubule in response to prostaglandin E2 were also measured. With few exceptions, all rabbits received 5 mg/day desoxycorticosterone acetate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
152
1
2

Year Published

1981
1981
1991
1991

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 348 publications
(164 citation statements)
references
References 32 publications
9
152
1
2
Order By: Relevance
“…Based on the data from separate in vitro perfusion studies of Stokes et al and Iino et al (3,4), it is clear that PGE2 inhibits sodium transport in the rabbit CCD in addition to its well known modulation of vasopressin-stimulated water permeability (6,22,23). Studies examining the interaction of PGE2 with vasopressin and cyclic AMPstimulated water permeability, suggest that PGE2 interacts with at least three different signaling mechanisms in the rabbit CCD: (a) a pathway linked to stimulation ofthe hydraulic conductivity via increased cAMP accumulation; (b) a second pathway coupled through Gi by which PGE2 inhibits hydrosmotic water flow in response to vasopressin by decreasing cAMP accumulation; (c) and finally, a third pathway by which PGE2 can also release cell calcium from intracellular stores.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the data from separate in vitro perfusion studies of Stokes et al and Iino et al (3,4), it is clear that PGE2 inhibits sodium transport in the rabbit CCD in addition to its well known modulation of vasopressin-stimulated water permeability (6,22,23). Studies examining the interaction of PGE2 with vasopressin and cyclic AMPstimulated water permeability, suggest that PGE2 interacts with at least three different signaling mechanisms in the rabbit CCD: (a) a pathway linked to stimulation ofthe hydraulic conductivity via increased cAMP accumulation; (b) a second pathway coupled through Gi by which PGE2 inhibits hydrosmotic water flow in response to vasopressin by decreasing cAMP accumulation; (c) and finally, a third pathway by which PGE2 can also release cell calcium from intracellular stores.…”
Section: Discussionmentioning
confidence: 99%
“…collecting duct * sodium * intracellular calcium Abundant evidence suggests that prostaglandin E2 (PGE2)1 is a major regulator ofsalt transport in the rabbit cortical collecting duct (CCD) PGE2 infusion into the renal artery of the dog increases Na+ and K+ excretion (1,2) without any major renal hemodynamic effect, suggesting a direct tubular action. Stokes et al were the first to demonstrate that PGE2 had a direct epitheHal action by showing that PGE2 decreased sodium transport in the rabbit (CCD) (3). lino and Imai confirmed that PGE2 reduced Na+ absorption and the lumen negative voltage in rabbit CCD when added to the peritubular surface (4).…”
Section: Introductionmentioning
confidence: 99%
“…Also in agreement with various other studies is the localization of the effect of indomethacin in the diluting segments of the distal tubule (Dusing et al, 1982;Iino & Imai, 1978;Higashihara etal., 1979;Stokes, 1979;Stokes & Kokko, 1977).…”
Section: Discussionmentioning
confidence: 99%
“…In vivo studies in man and animals have reported that GEIs induce natriuresis and renal hemodynamic changes.1)-4) The possible mechanisms of GEI-induced natriuresis in vivo have been suggested as follows: (1) vasodilatory and tubular actions due to reduction of angiotensin II and/or accumulation of kinins,3),9)-16) (2) vasodilatory and tubular actions due to stimulation of prostaglandin (PG) synthesis caused by an accumulation of kinins,17)- 19) and (3) formation is negligible in this system for feedback contol of renin release by AII. Since renin release from the isolated kidney is not influenced by captopril and SA446 (compared with the control group), captopril-induced natriuresis in the isolated perfused rat kidney may be independent of its inhibitory action on local AII formation.…”
Section: Discussionmentioning
confidence: 99%